2020
DOI: 10.1186/s12893-019-0673-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical analysis of Kimura’s disease in 24 cases from China

Abstract: BackgroundWe reviewed details of Chinese Kimura’s disease (KD) cases. A full clinical analysis was subsequently performed to improve the accuracy of clinical diagnosis and treatment of KD.MethodsA total of 24 patients with pathologically confirmed KD treated between March 2008 and March 2018 were reviewed retrospectively for clinical and histopathological analysis.ResultsIn the 24 KD cases, 20 were male and 4 were female with the age of onset ranging from 5 to 65 years. Lesion diameter ranged from 0.6 cm to 7 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(94 citation statements)
references
References 17 publications
5
75
1
1
Order By: Relevance
“… 13 16 Furthermore, a meta-analysis reported that the pooled prevalence of SSI in Ethiopia was 12.3%. 17 …”
Section: Introductionmentioning
confidence: 99%
“… 13 16 Furthermore, a meta-analysis reported that the pooled prevalence of SSI in Ethiopia was 12.3%. 17 …”
Section: Introductionmentioning
confidence: 99%
“…Da Vinci robotic surgery requires robotic equipment and has not been popularized worldwide. Our patented device can switch freely between single-port laparoscopy, complete laparoscopy, and small-incision hand-assisted laparoscopy, and we named it TULS [ 16 , 17 ]. It is especially suitable for procedures involving in complicated abdominal conditions and combined evisceration.…”
Section: Discussionmentioning
confidence: 99%
“…TULPG was developed by the authors and allows the operator to switch freely between single-port laparoscopic surgery, complete laparoscopic surgery, and small-incision hand-assisted laparoscopic surgery during the procedure. The specific method was described in our previous study [ 16 , 17 ]. In reference to the Japanese Gastric Cancer Treatment Guideline (fifth edition), we performed radical PG and completed separation of the stomach, the severing of blood vessels, and the dissection of lymph nodes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Occurrence of adhesions after upper and lower abdominal surgery ranges from 67–93% [ 4 , 5 ]. The mortality rate due to postsurgical adhesions can be high, especially among the elderly [ 6 ], and these complications can cause chronic pain and female infertility [ 7 , 8 ]. Prevention of adhesions aims to reduce inflammation and infection, which are the main triggers of their formation.…”
Section: Introductionmentioning
confidence: 99%